A temporalidade do texto anunciativo televisivo (TAT) - Pires Júnior, José Homero de Souza (Universidade do Vale do Rio do Sinos, 2006)
The thesis studies the television advertising text (TAT), texts in commercial breaks on TV, seeking to try out the hypothesis that the internal time of discourse works as a factor of passionate sensitivization on behalf of the persuasion that is inherent in the communicational processes. The main goal of this study is to carry out an analysis of the discourse internal time, based on semiotics time categories: chronological, rhythmic, mnesic, Kinematic time. The theoretical-methodological framework of the thesis lies on the semiotics of the School of Paris (greimasian semiotics). On such basis, television texts are analyzed within the media communicational perspective in accordance with the notions of narrative, time and passionateness. Guided mostly by this definite focus, the thesis also reflects about the object of communication in epistemological perspective and about other theoretical perspectives pertaining to the empirical object (television advertising text). The conclusions point to the heuristic p
Keywords: análise audiovisual; narrativa; semiótica; tempo interno discursivo; texto televisivo; mídia; audiovisual analisys; discourse internal time; narrative; semiotics; television text; media; Ciências Sociais Aplicadas